Comparing Host Plant Resistance, Engineered Resistance, and Insecticide Treatment for Control of Colorado Potato Beetle and Potato Leafhopper in Potatoes - Gerald M. Ghidiu; David S. Douches; Kimberly J. Felcher; Joseph J. Coombs (International Journal of Agronomy)
The Colorado potato beetle, Leptinotarsa decemlineata (Say) Order Coleoptera and the potato leafhopper, Empoasca fabae (Harris) Order Homoptera, are the major insect pests of potato in eastern North America. In two years of field trials, we compared the effectiveness of three pest management options for the control of Colorado potato beetle and potato leafhopper: natural host plant resistance (glandular trichomes), engineered resistance (Bacillus thuringiensis [Bt] Berliner cry3A gene) and a susceptible potato cultivar (Superior) with an at-planting application of the insecticide thiamethoxam. Similar and acceptable control of the Colorado potato beetle larvae was obtained with the Bt-cry3A lines and the thiamethoxam treated “Superior” variety. The glandular trichome cultivar had significantly less Colorado potato beetle damage than did the untreated “Superior” in 2004, although damage was significantly greater than in the Bt-cry3A lines and the insecticide-treated potatoes for both years, and was the only treatment that consistently had very little potato leafhopper damage. These data demonstrate that although each type of host plant resistance mechanism (Bt-cry3A or glandular trichomes) was as effective as the chemical control against one of the insects, neither provides adequate resistance to both Colorado potato beetle and potato leaf hopper.